PENGARUH LABEL HALAL DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PADA GLEAM CAFE DI PONTIANAK - Yunita, Rachma; Anshori, Aiyub; Nurlia (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the effect of halal labels and service quality on customer satisfaction at Gleam Cafe in Pontianak. The research uses a quantitative approach with associative causal methods. Data were collected through questionnaires distributed to 96 respondents who had visited Gleam Cafe at least twice. The sampling technique used purposive sampling. Data analysis was conducted using multiple linear regression with the help of SPSS. The results indicate that halal labels have a positive and significant effect on customer satisfaction. Service quality also has a positive and significant effect on customer satisfaction. Simultaneously, halal labels and service quality significantly influence customer satisfaction at Gleam Cafe in Pontianak. Service quality is the dominant factor affecting customer satisfaction. This study implies that culinary businesses need to maintain halal certification and improve service quality to increase customer trust and loyalty.